ANALISIS KINERJA KEUANGAN PERUSAHAAN KELAPA SAWIT GO PUBLIC DI INDONESIA (Kasus PT Astra Agro Lestari Tbk, PT Sampoerna Agro Tbk, PT PP London Sumatera Indonesia Tbk, PT Tunas Baru Lampung Tbk dan PT Sinar Mas Agro Resources and Technology Tbk) - Joko Purwono; Sri Sugyaningsih; Resty Istiarti (Trunojoyo University of Madura, 2015)
Palm Oil is one commodity plantation sub-sector plays an important role in the Indonesian economy. Aside from being a provider of raw materials and labor absorbing, oil palm is also a producer of foreign exchange after oil and gas. The purpose of this study was to evaluate the company's financial performance and identify the factors that affect the financial performance of palm oil companies go public. This research method is to use financial ratio analysis and analysis of Economic Value Added (EVA). Based on the analysis of financial ratios, PT Astra Agro Lestari Tbk and PT PP London Sumatra Indonesia Tbk has the best financial performance. While other companies have a poor financial performance due to high debt and poor sales of the company. Based on analysis of Economic Value Added, the financial performance of palm oil companies went public during the three-year period show declining performance and negative in 2012. PT Sinar Mas Agro Resources and Technology Tbk has the best performance over the three-year observation period.